Compounds from culture broth of marine bacterium Micromonospora sp. (G047) - Nam, Vu Van; Mai Huong, Doan Thi; Minh, Chau Van; Cuong, Pham Van (Vietnam Journal of Chemistry, 2017)
Five compounds L-phenyl alanine (1), 1-methyl-6-acetyl-α-D-glucopyranoside (2), thymine (3), uracil (4), and (2R,3S)-butane-2,3-diol (5) were isolated and characterized from the culture broth of the marine bacterium Micromospora sp. (G047 strain), which was isolated from the sediment collecting from the coast of Co To – Quang Ninh. The structures of all isolates were determined by spectroscopic analysis including MS and 2D NMR, as well as by comparison with reported data in the literature. Compound 2 has been previously synthesized, however, this is the first its report from a natural source. Keywords. Micromospora sp., marine bacterium, 1-methyl-6-acetyl-α-D-glucopyranoside, thymine, uracil, L-phenyl alanine